Correlation between mandibular bone density with CD4-T cells and duration of HAART in HIV-infected children - Maulani, Intan; Primarti, Risti Saptarini; Sufiawati, Irna; Indriyanti, Ratna; Andiesta, Niekla Survia; Riyanti, Eriska (Universitas Padjadjaran, 2021)
Introduction: Perinatal HIV infection has decreased adverse bone health effects and mineral accrual. HIV-infected patients have a multifactorial origin, including HIV bone cell infections, inflammatory cytokine effects on osteoblast and osteoclast activity, and HAART. The research objective was to analyze the correlation between the mandibular bone density with CD4 T-cells and duration of HAART in HIV-infected children. Methods: The mandibular bone density in the HIV-infected pediatric population was evaluated using a panoramic radiograph. The research design was a cross-sectional and univariate regression analysis for the sampling method. Mandibular density analysis using Spearman and Pearson correlation and HAART duration using Kendall correlation. Thirty-five HIV-infected children and seventeen non-HIV-infected children were recruited. Results: This study showed the significant correlation between Mandibular cortical shape index of HIV-infected and non-HIV children and there is a significant correlation between fractal dimension of HIV-infected and non-HIV children (p<0.05). There is no significant correlation between mandibular bone density and the CD4 level(p<0.05). Mandibular bone density and duration HAART and have a significant correlation (p<0.001). This research showed correlations between mandibular bone density CD4 T-cells and duration of HAART in HIV-infected children. Conclusion: There is no correlation between the mandibular bone density and CD4 T-cells count, however, there is a correlation between the mandibular bone density and duration of HAART in HIV-infected children.